The Effects of 8 weeks of high intensity interval training and high intensity functional training on physical performance and volume of firefighters' self-contained breathing apparatus - Afshin Seraji; Sajad Ahmadizad; David Cornell (Shahid Beheshti University, 2024)
Background and Purpose: Firefighting is a high-risk profession that requires high physical fitness, and it is important to have regular exercise to maintain optimal physical fitness and health. However, there is a little research on the best types and methods of training to improve the performance of firefighters and reduce the volume of self-contained breathing apparatus (SCBA) used in duty. Therefore, the purpose of this study was to investigate and compare the effect of 8 weeks of high-intensity interval and functional training on cardiorespiratory fitness (VO2max) and the used volume of SCBA in firefighters.Materials and Methods: Thirty-nine firefighters working in the fire department of Tehran participated in the study and were randomly allocated in the three groups of control, HIIT and HIFT. Subjects in HIIT group performed 8 weeks of Tabata exercises with body weight, which were 4 exercises in the first two weeks and were increased to 6 and 8 exercises in the 6th and 8th weeks, respectively. In each session, they had 10 min general warm up, thereafter they performed 8 sets of each exercise, where sets included 20 s activity followed by 10 s rest and 2 min rest was allowed between exercises. Subjects in HIFT group had similar program to the HIIT group, with the exception that the exercises they performed were those exercises in the standard simulated test for firefighters which were performed based on the Tabata methods (20 s activity followed by 10 s rest). Two days before training and 48 hours after the last training session the VO2max test (Bruce's protocol) and simulated firefighting test were carried out.Results: The statistical analysis of the data showed that HIFT and HIIT caused a significant increase in maximal oxygen uptake (VO2max) and performance, and a significant decrease in the volume of SCBA used in firefighters (p<0.05), though, these changes were not significantly different between HIIT and HIFT groups (p<0.05). VO2max increased by 6.35% and 4.26% in HIFT and HIIT groups, and performance increased by 5.21 and 4.74%, following HIFT and HIIT, respectively. In addition, VO2/HR increased by 11.64 and 6.52% in HIIT and HIIT groups, respectively, while, the volume of SCBA used decreased by 14.41% and 11.44%, respectively. However, the results of repeated measures of ANOVA showed no significant between-group differences for RER (P=0.269), HR (P=0.595), VE (P=0.392), VE/VO2 ratio (P0.778) =) and VE/VCO2 ratio (P=0.778).Conclusion: According to the results of the present study it could be concluded that 8 weeks of HIFT and HIIT can improve cardiorespiratory fitness (VO2max), performance, and the volume of SCBA used in firefighters, and that performing these types of training based on the Tabata's method is advised to firefighters.